2011
DOI: 10.1371/journal.pone.0027953
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual Immunization with M2-Based Vaccine Induces Broad Protective Immunity against Influenza

Abstract: BackgroundThe ectodomain of matrix protein 2 (M2e) of influenza A virus is a rationale target antigen candidate for the development of a universal vaccine against influenza as M2e undergoes little sequence variation amongst human influenza A strains. Vaccine-induced M2e-specific antibodies (Abs) have been shown to display significant cross-protective activity in animal models. M2e-based vaccine constructs have been shown to be more protective when administered by the intranasal (i.n.) route than after parenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 48 publications
3
59
0
Order By: Relevance
“…M2 is a 97 aa protein with a single TMD which forms disulphidelinked tetramers in membranes (Holsinger & Lamb, 1991;Sugrue & Hay, 1991). The N-terminal 25 aa are located on the surface of the plasma/virion membrane and are highly conserved; considerable efforts have been focused on this region as a pan-influenza vaccine strategy (Neirynck et al, 1999;Shim et al, 2011). The TMD (aa 25-46) is followed by an amphipathic helix (aa 47-62) and the remaining cytosolic domain.…”
Section: Iav M2mentioning
confidence: 99%
“…M2 is a 97 aa protein with a single TMD which forms disulphidelinked tetramers in membranes (Holsinger & Lamb, 1991;Sugrue & Hay, 1991). The N-terminal 25 aa are located on the surface of the plasma/virion membrane and are highly conserved; considerable efforts have been focused on this region as a pan-influenza vaccine strategy (Neirynck et al, 1999;Shim et al, 2011). The TMD (aa 25-46) is followed by an amphipathic helix (aa 47-62) and the remaining cytosolic domain.…”
Section: Iav M2mentioning
confidence: 99%
“…Indeed, other surface influenza proteins, including the NA and M2 protein, are also likely to be targets for ADCC (49). Vaccination studies performed using influenza M2 protein suggest a protective role mediated by nonneutralizing Abs (50)(51)(52). The M2-specific Abs were shown to protect against both homologous and heterologous influenza virus challenge in the mouse model.…”
Section: Cd56mentioning
confidence: 99%
“…Previous studies have shown that the i.n. mucosal route is superior to systemic administration for inducing cross-protective immunity in mice (7,30,48). Other studies have focused on chemical and genetic conjugates (carrier molecules or virus particles) or a combination of DNA and recombinant or live influenza vaccines to improve cross-protection (49)(50)(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies that demonstrated that i.n. vaccination with 3M2eC plus CT induced Abs that could improve mortality but not morbidity (7). In contrast, mice that received sM2HA2 with CA-PMQ showed negligible signs of disease and only a slight and transient loss of weight.…”
Section: Ca-pmq Enhances Sm2-and Ha2-specific T Cell Responses Inducementioning
confidence: 91%
See 1 more Smart Citation